PENGARUH KUALITAS LAYANAN DAN NIAT TERHADAP KEPATUHAN WAJIB PAJAK DENGAN TAHUN PEMBINAAN WAJIB PAJAK (TPWP) SEBAGAI PEMODERASI (Studi Kasus Pada UMKM Kota Semarang) - Amalia Rahmawati, 12.05.52.0001; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2016)
This study aims to test and analyze the effect of tax quality service, intention, and year coaching the taxpayer on the tax compliance with years of coaching the taxpayer as moderating. The population in this study are personal tax payers list in Semarang that have UMKM. Sampling was done using purposive sampling method and sample size of 102 respondens. Personal tax payers list in Semarang that have UMKM. The primary data using moderating regression analisys model. The result showed that the tax quality service not significant positive on the tax compliance. Year coaching the taxpayer and intention a significant positive on the tax compliance. And year coaching the taxpayer moderating the effect intention on tax compliance.Keywords: Tax Quality Service, Intention, Year Coaching The Taxpayer, Tax Compliance